2009
DOI: 10.1128/aac.00779-08
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CD4+T Lymphocytes, CD8+T Lymphocytes, or B Lymphocytes Has Different Effects on the Efficacy of Posaconazole and Benznidazole in Treatment of Experimental AcuteTrypanosoma cruziInfection

Abstract: We investigated the influence of CD4؉ T lymphocytes, CD8 ؉ T lymphocytes, and B lymphocytes on the efficacy of posaconazole (POS) and the reference drug benznidazole (BZ) during treatment of acute Trypanosoma cruzi infection in a murine model. Wild-type mice infected with T. cruzi and treated with POS or BZ presented no parasitemia, 100% survival, and 86 to 89% cure rates, defined as the percentages of animals with negative hemocultures at the end of the observation period. CD4؉ -T-lymphocyte-knockout (KO) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
2
27
0
6
Order By: Relevance
“…Several factors could be in play. A majority of studies that previously reported successful clearance of murine T. cruzi infections by posaconazole employed mice in early acute phase, with treatment starting as early as 1 day after the infection (8,9,33,34,37,38). It is possible that T. cruzi parasites in longer-term infections respond differently to treatment with posaconazole than parasites in early acute infections.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several factors could be in play. A majority of studies that previously reported successful clearance of murine T. cruzi infections by posaconazole employed mice in early acute phase, with treatment starting as early as 1 day after the infection (8,9,33,34,37,38). It is possible that T. cruzi parasites in longer-term infections respond differently to treatment with posaconazole than parasites in early acute infections.…”
Section: Discussionmentioning
confidence: 95%
“…In that study, treatment failure was not evaluated by using an immunosuppression protocol, and it is possible that the sensitivity of parasite detection in that study was lower than in the current study. Failure to perform immunosuppression after the treatment also limits the sensitivity of three other studies from this list (33,34,38).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that the anti-T. cruzi activity of POS in a murine model of acute Chagas disease is much less dependent on interferon-γ than that of BZN (Ferraz et al 2007). It has also been shown that ablation of TCD4 + , TCD8 + and B lymphocytes has distinct effects on POS and BZN activity in the same experimental model (Ferraz et al 2009). POS efficacy was especially dependent on the presence of functional TCD8 + cells, but relatively insensitive to the absence of LB cells, yet the reverse was true for BZN; the activity of both drugs was markedly reduced in the absence of TCD4 + cells.…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
“…POS efficacy was especially dependent on the presence of functional TCD8 + cells, but relatively insensitive to the absence of LB cells, yet the reverse was true for BZN; the activity of both drugs was markedly reduced in the absence of TCD4 + cells. These results were interpreted in terms of the different parasite stages preferentially targeted by the two drugs (intracellular amastigotes by POS, extracellular trypomastigotes by BZN) and distinct cooperation patterns with the host's immune system (Ferraz et al 2009). An independent study in a similar experimental model found that POS was more effective than BZN in preventing heart damage and promoting a trypanocidal immune response (Olivieri et al, unpublished observations).…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
“…O Nifurtimox é produzido pela Bayer para tratamento da doença de Chagas em alguns países da América Latina e, além disso, para tratamento da tripanossomíase africana Gambiense no continente africano (Jannin e Villa, 2007). A ação antiparasitária do nifurtimox está associada à geração de espécies reativas de oxigênio (EROs), tais como ânion superóxido e peróxido de hidrogênio (Docampo, 1990;Maya et al, 2007;Dias et al, 2009) (Urbina et al, 1998;Ferraz et al, 2007Ferraz et al, , 2009) e o ravuconazol (Urbina e Docampo, 2003;Diniz Lde et al, 2010) dos quais são os candidatos mais avançados para o desenvolvimento da nova droga anti -T. cruzi, partindo para ensaios clínicos dentro de pouco tempo (Urbina, 2010). Compostos que inibem a enzima cisteína protease, ou mais precisamente, a cruzipaína, também são canditados para o desenvolvimento de quimioterapias.…”
Section: Drogas Disponíveisunclassified